Preemptive Infiltration of Local Anesthetics During Vaginal Hysterectomy: A Systematic Review and Meta-analysis of Randomized Controlled Trials. Issue 1 (January 2023) - Zacharakis, Dimitrios; Prodromidou, Anastasia; Douligeris, Athanasios; Athanasiou, Stavros; Hadzilia, Sophia; Kathopoulis, Nikolaos; Athanasiou, Veatriki; Grigoriadis, Themos
Abstract : (Abstracted from Urogynecology 2022;28:667–678) Undergoing pelvic floor reconstructive surgery bears a lifetime risk between 14% and 19%, with a significantly higher risk in elderly and postmenopausal women. The traditional preferred surgical approach for pelvic floor disorders (PFDs) is vaginal hysterectomy (VH) with or without pelvic floor repair.